Ultraviolet Functionalization of Electrospun Scaffolds to Activate Fibrous Runways for Targeting Cell Adhesion - Girão, André F.; Wieringa, Paul; Pinto, Susana C.; Marques, Paula A. A. P.; Micera, Silvestro; van Wezel, Richard; Ahmed, Maqsood; Truckenmueller, Roman; Moroni, Lorenzo (Frontiers in Bioengineering and Biotechnology, 2019)
A critical challenge in scaffold design for tissue engineering is recapitulating the complex biochemical patterns that regulate cell behavior in vivo. In this work, we report the adaptation of a standard sterilization methodology – UV irradiation – for patterning the surfaces of two complementary polymeric electrospun scaffolds with oxygen cues able to efficiently immobilize biomolecules. Independently of the different polymer chain length of poly(ethylene oxide terephthalate)/poly(butylene terephthalate) (PEOT/PBT) copolymers and PEOT/PBT ratio, it was possible to easily functionalize specific regions of the scaffolds by inducing an optimized and spatially controlled adsorption of proteins capable of boosting the adhesion and spreading of cells along the activated fibrous runways. By allowing an efficient design of cell attachment patterns without inducing any noticeable change on cell morphology nor on the integrity of the electrospun fibres, this procedure offers an affordable and resourceful approach to generate complex biochemical patterns that can decisively complement the functionality of the next generation of tissue engineering scaffolds.